PENGEMBANGAN PERANGKAT PEMBELAJARAN STRATEGI QUICK ON THE DRAW DENGAN MASALAH OPEN ENDED UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATERI PRISMA DAN LIMAS - Suryadinata, Nurain (AKSIOMA JURNAL PENDIDIKAN MATEMATIKA, 2015)
The aim of this research to gain the result of developing instructional sets through quick on the draw with open ended problem of pyramid and prism subject validly, practically, and effectively. The learning instrument deve-lopment using Plomp model. TKKM data processed by t test, and the proportion of z.The instructional sets valid based on the average score of validity: Syllabus 4.0; Lesson Plan 4.2; Supplementary Books 4.3; Studentsâ Worksheets 4.3; and creative thinking test on mathematics was valid, the level of difficulty was balance, and distinctive feature was significant and reliable. The instructional sets were practical by gaining average score 3,87, the implementation of learning process was good. Students and teachers had positive responses. The instructional sets were effective by gaining: studentsâ creative thinking competence of mathematics beyond the KKM; creative thinking abilities of students who were given a quick on the draw learning with open ended problems better than students were given the conventional learning; and the improvement of creative thinking competence of students who were given a quick on the draw learning with open ended problems better than students were given the conventional learning.